Evaluation of clinical response to empirical antimicrobial therapy on day 7 and mortality in the intensive care unit: sub‐analysis of the DIANA study Japanese data - Chie Tanaka; Takashi Tagami; Masamune Kuno; Kyoko Unemoto; DIANA Study Japanese Group (Acute Medicine & Surgery, 2023)
Aim It is not clear whether evaluating the clinical response to antibiotic use at day 7 among critically ill patients accurately predicts outcomes. We aimed to evaluate the relationship between clinical response to the initial empiric therapy on day 7 and mortality. Methods The determinants of antimicrobial use and de‐escalation in critical care (DIANA) study was an international, multicenter, observational study on antibiotic use in the intensive care unit (ICU). ICU patients ages over 18 years in whom an empiric antimicrobial regimen in Japan was initiated were included. We compared patients who were evaluated as cured or improved (“effective”) 7 days after starting antibiotic treatment with patients who were evaluated as deteriorated (“failure”). Results Overall, 217 (83%) patients were in the effective group, and 45 (17%) were in the failure group. Both the infection‐related mortality rate in the ICU and the in‐hospital infection‐related mortality rate in the effective group were lower than those in the failure group (0% versus 24.4%; P < 0.01 and 0.5% versus 28.9%; P < 0.01, respectively). Conclusion Assessment of efficacy of empiric antimicrobial treatment on day 7 may predict a favorable outcome among patients suffering from infection in the ICU.